RESPONSES OF PARICÁ SEEDLINGS TO WATER STRESS - Duarte, Daiane Marques; Rocha, Gabriela Teodoro; Lima, Fernanda Borges de; Matos, Fábio Santos; Rodrigues, Fabricio (Floresta, 2016)
The present study objective was identifying mechanisms of response to water deficit of paricá seedlings. The experiment was conducted in a greenhouse, in 8-liter pots, with substrate consisting of soil (dystrophic Red-Yellow Latosol), in randomized block design, with five different irrigations based on the evapotranspiration of the plants (20, 40, 60, 80 and 100%), with six replications. The plants were irrigated daily, with a water volume corresponding to 100% of the evapotranspired water, and, at 90 days after germination, subjected to ten days of water deficit, after that irrigated during ten days with the different percentages of evapotranspiration, then evaluated. The following variables were measured: number of leaves (NL), plant height (PH), stem diameter (SD), total biomass (TB), total daily transpiration (TDT), total chlorophyll (TC), carotenoids (CAR), root mass ratio (RMR), leaf mass ratio (LMR) stem mass ratio (SMR). Concluded that paricá seedlings response to water deficit with slowing down of dehydration, with reduction of content of carotenoids and increase in root volume. As a consequence of water stress, they reduce the number of leaves, stem diameter, plant height, and, of course, total biomass, aiming at maintaining the internal water, indicating low ability to tolerate stress.